Florida Forest Landowner Preferences for Carbon Offset Program Characteristics - José R. Soto; Damian C. Adams; Francisco J. Escobedo (EDIS)
This 5-page fact sheet explains how carbon-offset programs operate and examines their benefits to landowners and the environment, especially in Florida and the southeast US. A summary of a recent study of Florida forest landowners is used to better reveal views on forest carbon-offset programs and their willingness-to-accept monetary compensation for their enrollment in such programs. Written by José R. Soto, Damian C. Adams, and Francisco J. Escobedo, and published by the UF Department of School of Forest Resources and Conservation, September 2014.